Kebijakan Inovasi Manajemen Pendidikan dalam Meningkatkan Mutu Pondok Pesantren di Pondok Pesantren Nurul Huda Mangunsari Tekung Lumajang - Imroatul Hasanah; Titin Nurhidayati; Daris Salama Ulin Nuha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze educational management innovation policies in improving the quality of education at Nurul Huda Mangunsari Islamic Boarding School (Pondok Pesantren), located in Tekung. As an Islamic educational institution, the pesantren plays an important role in character building and the development of Islamic knowledge. However, the demands of modern developments require pesantren to implement innovations in their educational management systems in order to enhance institutional quality and produce competent graduates.This study employed a qualitative approach using a case study research design. Data were collected through observation, interviews, and documentation involving the pesantren leader, teaching staff, and students (santri).The findings indicate that the educational management innovation policies implemented at the pesantren include strengthening institutional management systems, improving teacher competencies, integrating the pesantren curriculum with formal education curricula, and utilizing technology in educational administration. The implementation of these policies has had a positive impact on improving educational quality, both in terms of academic achievement and character development among students. Nevertheless, several challenges remain, including limited infrastructure and human resources. Therefore, the development of sustainable educational management strategies is necessary to support the continuous improvement of educational quality in Islamic boarding schools in the future.